Rhabdomyosarcoma of lip - issues of subtyping, morphology and immunohistochemistry versus molecular studies: a case report with review of literature - Alexander, Leon; Ravindran, Hiran Kattilaparambil; George, Juliet (International Surgery Journal, 2020)
Rhabdomyosarcoma (RMS) is a malignant soft tissue tumour occurring most frequently in younger age groups. Study presented a rare case of spindle cell Rhabdomyosarcoma of the upper lip involving the commissure area. In this case report after successful surgical excision, the patient underwent extensive postoperative histopathological studies including special stains and immunohistochemistry. Genotype studies (reverse transcription polymerase chain reaction) were done to help in subtyping and prognostication, and it turned out to be a surprise as it showed positivity for PAX3-FOXO1 t (2;13) translocation which is almost exclusively seen with alveolar RMS. After that he successfully underwent chemotherapy and radiotherapy as it was an aggressive variant and has been disease free for the past 2 years. The author hopes that this case report will highlight the importance of high clinical suspicion in head and neck masses presenting in pediatric age group and to not rely solely on biopsy reports to confirm diagnosis, so that early detection will lead to successful therapy and outcome as exemplified in this case.